Enhancing High School Character Development through the Integration of Songket Melayu Riau Wisdom in Character Education - Nandisa, Adelin; Miftahuddin, Miftahuddin; Dwi Yuliantri, Rhoma; Fikri, Asyrul (AL-ISHLAH: Jurnal Pendidikan, 2024)
Character education rooted in indigenous knowledge offers a remedy for instilling traditional values into students' character development. The local wisdom of Riau Malay Songket is one of the local wisdom that provides a strong cultural foundation for students to build a solid identity and understand the importance of cultural diversity. The objective of this study is to evaluate how effective character education based on the local wisdom of Songket Melayu Riau is in shaping the character of high school students. This research uses quantitative methods with a one-group pretest-posttest Design approach. Purposive sampling strategies were used to choose 30 class X students from SMAN 1 Riau as the research subjects. A questionnaire that the researcher created was employed as the study tool. The data analysis for this study used the paired t-test, N-Gain test, homogeneity test, and normality test. With a significance level below 0.05, the study's findings show a significant difference in students' character development before and after character education based on Songket Melayu Riau's local wisdom. Furthermore, the N-Gain evaluation indicates a score of 31.53, indicating a 32% rise in quantifiable character. Therefore, implementing character education aligned with Songket Melayu Riau's traditional wisdom effectively develops students' moral character.